2016
DOI: 10.1007/s00253-016-7660-z
|View full text |Cite
|
Sign up to set email alerts
|

Fungi as a source of natural coumarins production

Abstract: Natural coumarins and derivatives are compounds that occur naturally in several organisms (plant, bacteria, and fungi) consisting of fused benzene and α-pyrone rings. These compounds show high technological potential applications in agrochemical, food, pharmaceuticals, and cosmetics industries. Therefore, the need for bulk production of coumarins and the advancement of the chemical and pharmaceutical industries led to the development of synthetic coumarin. However, biotransformation process, synthetic bioengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 86 publications
(150 reference statements)
2
30
0
Order By: Relevance
“…Coumarins (1,2-benzopyrone or benzopyran-2-one) are heterocyclic compounds present in many plants (Angiospermas, Apiaceae, Rutaceae, and Asteraceae) (Venugopala, Rashmi, & Odhav, 2013) fungi (Agaricus sp., Armillariella tabescens, and Penicillium) (Costa, Tavares, & Oliveira, 2016), and bacteria (Streptomyces spheroides and Streptomyces niveus) (Steffensky, Mühlenweg, Wang, Li, & Heide, 2000). The isocoumarins are structurally similar to coumarins, differing only by the orientation of the lactone.…”
mentioning
confidence: 99%
“…Coumarins (1,2-benzopyrone or benzopyran-2-one) are heterocyclic compounds present in many plants (Angiospermas, Apiaceae, Rutaceae, and Asteraceae) (Venugopala, Rashmi, & Odhav, 2013) fungi (Agaricus sp., Armillariella tabescens, and Penicillium) (Costa, Tavares, & Oliveira, 2016), and bacteria (Streptomyces spheroides and Streptomyces niveus) (Steffensky, Mühlenweg, Wang, Li, & Heide, 2000). The isocoumarins are structurally similar to coumarins, differing only by the orientation of the lactone.…”
mentioning
confidence: 99%
“…[15] Additionally, we proposed a plausible biosynthetic pathway of 1. The biosynthetic route starts from glucose via phenylalanine to yield umbeliferone [24] which undergoes alkylation [25,26] to obtain 1 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[41,42,24] These secondary metabolites have many bioactivities such as antiacetylcholinesterase, anti-bacterial, anti-cancer, anti-coagulant, anti-fungal, anthelmintic, anti-inflammatory, anti-HIV, antimicrobial, anti-oxidant and anti-viral activities. [41,42,24,43] Coumarins are utilized in wide range of applications, not only as pharmaceuticals but also as cosmetics, fragrances, agrochemicals, insecticides, in food industry and in color technol-ogy. [24,44] Additionally, coumarins have been used in pharmaceutical industry as precursors in the synthesis of anticoagulant agents since 1868.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of derivatives including furan rings and pyran rings has been reported from bacteria, fungi and plants. As it regards fungi, coumarins have been up to now isolated from several species both in Ascomycota and Basidiomycota, including polypores (Costa et al 2016); nevertheless, chlorination has been reported from F. officinalis only, despite chlorinated coumarins are known in plants (Guz et al 2001;Patnam et al 2005).…”
Section: Chlorinated Coumarinsmentioning
confidence: 99%